Terahertz Time Domain, Raman and Fourier Transform Infrared Spectroscopy of Acrylamide, and the Application of Density Functional Theory. (5th January 2014) - Ullah, Ramzan; Khan, Salah Ud-Din; Aamir, Muhammad; Ullah, Rasheed
Abstract : We present terahertz time domain spectra of acrylamide in the frequency range from 0.2 to 2 THz with nearly constant refractive index having an average value of 1.33 and an absorption coefficient. Raman (95–3000 cm −1 ) and FTIR (450–4000 cm −1 ) spectra also show good agreement with density functional theory (DFT) B3LYP 6-311G++ (3df 3pd) calculations except C-H and N-H stretching frequencies even after scaling with scale factor of 0.9679. We use MOLVIB to rescale such frequencies to match experimental values.